Предмет: Алгебра,
автор: mstossel
упростите выражение:
1) -5a - (2a - (3a - 5))
2) 2 - (5x - 3)(x - 8)
3) (3x - 2)(-x^2 + x - 4)
4) (4a)^2 - a^3(2 - 3a)
Ответы
Автор ответа:
0
1) -5a - (2a -3a + 5) = -5a -2a +3a -5= -4a-5
2) 2 -(5x²-40x-3x+24)= 2-5x²+40x+3x-24=-5x²43x-22
3) -3x³+3x²-12x+2x²-2x+8= -3x³+5x²-14x+8
4) 16a²-2a³+3a∧4
2) 2 -(5x²-40x-3x+24)= 2-5x²+40x+3x-24=-5x²43x-22
3) -3x³+3x²-12x+2x²-2x+8= -3x³+5x²-14x+8
4) 16a²-2a³+3a∧4
Автор ответа:
0
-5a-(2a-3a+5)=-5a+a-5=-4a-5
2-(5x^2-43x+24)=2-5x^2+43x-24=-5x^2+43x-22
-3x^3+3x^2-12x+2x^2-2x+8=-3x^3+5x^2-14x+8
16a^2-2a^3+3a^4
2-(5x^2-43x+24)=2-5x^2+43x-24=-5x^2+43x-22
-3x^3+3x^2-12x+2x^2-2x+8=-3x^3+5x^2-14x+8
16a^2-2a^3+3a^4
Похожие вопросы
Предмет: Литература,
автор: sstar3729
Предмет: Қазақ тiлi,
автор: shaukermirlan
Предмет: Литература,
автор: aksuluerbolatkyzy4
Предмет: Геометрия,
автор: Nastia1500